2016
DOI: 10.1002/alr.21790
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin B12 deficiency on olfactory function

Abstract: In this study, we showed for the first time that olfactory dysfunction may be present in patients with vitamin B12 deficiency. Apart from a negative correlation of age with odor identification score, none of the other parameters studied showed correlations with olfactory dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…1453 Although no blood tests exist for PD at present, a promising blood test for AD has been recently developed. 1454 When dealing with other causes of OD, eg, toxins, such as heavy metals or lead, 1455 Sjögren syndrome, 1456 DM, 1457 Wilson disease, 1458 and liver cirrhosis, 1459 clinical suspicion needs to guide the physician on which test(s) to order or whether to refer the patient to a colleague with expertise in a specific underlying etiology.…”
Section: G Role Of Bloodwork/lab Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…1453 Although no blood tests exist for PD at present, a promising blood test for AD has been recently developed. 1454 When dealing with other causes of OD, eg, toxins, such as heavy metals or lead, 1455 Sjögren syndrome, 1456 DM, 1457 Wilson disease, 1458 and liver cirrhosis, 1459 clinical suspicion needs to guide the physician on which test(s) to order or whether to refer the patient to a colleague with expertise in a specific underlying etiology.…”
Section: G Role Of Bloodwork/lab Valuesmentioning
confidence: 99%
“…The most commonly used corticosteroid was oral prednisolone with a starting dose of 30 to 60 mg/day and a 2-week taper. Five cohort studies with a total of 553 patients demonstrated that 16.4% to 49.6% of patients treated with systemic steroids had a significant improvement in olfaction threshold measurements 1728,[1743][1744][1745][1746] with two studies demonstrating clinically meaningful improvements of TDI in 12% to 29% of patients. 1728,1746 Systemic steroids were not beneficial in a small retrospective case series of patients who were nonrespondent to topical therapy 1747 and an RCT of patients with PTOD, although this study may have been underpowered.…”
mentioning
confidence: 99%
“…Воздействие витаминов групп В на обмен ацетилхолина, дофамина, серотонина и γ-аминомасляной кислоты, восстановление миелиновых оболочек нервов, торможение воспаления позволяет рассматривать их как перспективные препараты для терапии неврологических проявлений COVID-19. Кроме того, терапия витамином В 12 способствует преодолению аносмии [52] -неврологического симптома, встречающегося у 80 % пациентов с COVID-19 [53].…”
Section: тиамин и противодействие сепсисуunclassified
“…Other causes include head injuries, illnesses such as cancer and infectious disease, environmental hazards such as insecticides, and medications (i.e., some antibiotics and antihistamines) [5]. Nutritional deficiencies also contribute to these deteriorations including trace metal deficiencies such as copper [6], zinc [7], and magnesium [8] and some vitamin deficiencies including Vitamin A [9], E [10], and B12 [11].…”
Section: Introductionmentioning
confidence: 99%